Torque Teno virus DNA is found in the intracranial aneurysm wall—Is there a causative role? - Rabelo, Nícollas Nunes; Yoshikawa, Marcia Harumy; Telles, João Paulo Mota; Coelho, Giselle; de Souza, Caio Santos; de Oliveira, Natan Ponzoni Galvani; Mendoza, Tania Regina Tozetto; Braz-Silva, Paulo Henrique; Boechat, Antonio Luiz; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Frontiers in Medicine, 2023)
Objective: Torque Teno Virus (TTV) is a recently discovered virus with high prevalence worldwide, that has been associated with vascular diseases. The aim of this study is to investigate the prevalence of TTV molecular DNA in the intracranial aneurysm (IA) artery walls. Method: Samples of IA walls were collected after microsurgical clipping from 35 patients with IA (22 ruptured /13 unruptured cases). The samples were submitted to molecular DNA extraction using the EasyMag automatized extractor and performed with Qiagen DNA extraction Minikit 250. The samples underwent PCR examination with primers for β-globin as internal control using the Nanodrop® 2000 spectrophotometer. A quantitative (real-time) PCR with TTV-specific primers was performed. Clinical and radiological data of patients included was collected. Results: TTV was detected in 15 (42.85%) cases, being 10 (45.4%) ruptured and 5 (38.4%) unruptured (p=0.732) lesions. Multiple IAs accounted for 14 (40%) cases. Five cases (17.2%) had TTV+ and multiple aneurysms (p=0.73). Association between presence of virus and aneurysm rupture was not statistically significant (p=0.96). Conclusions: This study demonstrated a relatively high prevalence of viral DNA in the walls of IAs. This is the first study to identify the presence of TTV DNA in IA’s samples, which was found more often in ruptured lesions. This is an exploratory study, therefore, larger studies are required to clarify the relationships between inflammation, viral infection, IA formation and rupture.